Intestinal antispasmodic effects of three Argentinian plants: Hypericum connatum, Berberis ruscifolia and Cecropia pachystachya: mechanisms of action and comparison with the effects of Brugmansia arborea - Matera, Soledad Inés (2016)
Some medicinal plants are used in Argentina to reduce gastrointestinal symptoms as antispasmodics, but notall these effects were validated. This work studied the effects of three native plants as the ethanolic tinctures(T) of Hypericum connatum and Berberis ruscifolia, as well as the acqueous crude extracts (A.c.e) of Cecropiapachystachya, and compared the mechanisms with those of the peruvian plant Brugmansia arborea inisolated rat intestines. The first three plants demonstrated to have antispasmodic effect mainly due to thenon-competitive blockade of the agonist-induced contraction and calcium influx to the smooth muscle,which was associated to the presence of flavonoids. H. connatum also induced the release of prostaglandinswhich cause intestinal contraction, and NO which cause peristalsis, in a way that the blockade of bothmechanisms potentiated the relaxant effect of the T-H.c. In contrast, the A.c.e of Brugmansia arboreashowed to be a competitive antagonist of muscarinic receptors in the isolated intestine, in agreement withthe presence of tropane alkaloids. Moreover, H. connatum and C. pachystachya also produced certainsedation, which could contribute to the antispasmodic effect. The tincture of Hypericum connatum, but notthat of Berberis ruscifolia, reduced the spontaneous locomotion and exploration of mice in the open-fieldtest, at doses of 200 mg leaves/Kg. Results suggest that the three native plants exhibited an importantantispasmodic effect mainly due to non-competitive antagonism of the agonist and of Ca2+-influx to smoothmuscle.